2017
DOI: 10.1186/s40851-017-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

On the development of the chondrocranium and the histological anatomy of the head in perinatal stages of marsupial mammals

Abstract: An overview of the literature on the chondrocranium of marsupial mammals reveals a relative conservatism in shape and structures. We document the histological cranial anatomy of individuals representing Monodelphis domestica, Dromiciops gliroides, Perameles sp. and Macropus eugenii. The marsupial chondrocranium is generally characterized by the great breadth of the lamina basalis, absence of pila metoptica and large otic capsules. Its most anterior portion (cupula nasi anterior) is robust, and anterior to it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 149 publications
(205 reference statements)
3
49
0
Order By: Relevance
“…Our own experience shows that haematoxylin and eosin plus Alcian Blue staining might be most useful to differentiate mesenchymal condensations and chondrifications in early development (Yaryhin & Werneburg, ), whereas Azan staining after Haidenhain is particularly useful for late ontogeny, when bones have already started to form (Mulisch & Welsch, ). Another important issue is the diverse terminology of chondrocranial anatomy between major taxonomic groups, which might represent a hindrance to studies of this subject. Examples were highlighted by Sánchez‐Villagra and Forasiepi (). Moreover, for exact character definition, it is extremely important to know more than just bone anatomy.…”
Section: Problems Of Studying Comparative Craniogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Our own experience shows that haematoxylin and eosin plus Alcian Blue staining might be most useful to differentiate mesenchymal condensations and chondrifications in early development (Yaryhin & Werneburg, ), whereas Azan staining after Haidenhain is particularly useful for late ontogeny, when bones have already started to form (Mulisch & Welsch, ). Another important issue is the diverse terminology of chondrocranial anatomy between major taxonomic groups, which might represent a hindrance to studies of this subject. Examples were highlighted by Sánchez‐Villagra and Forasiepi (). Moreover, for exact character definition, it is extremely important to know more than just bone anatomy.…”
Section: Problems Of Studying Comparative Craniogenesismentioning
confidence: 99%
“…(4) Another important issue is the diverse terminology of chondrocranial anatomy between major taxonomic groups, which might represent a hindrance to studies of this subject. Examples were highlighted by Sánchez-Villagra and Forasiepi (2017). Moreover, for exact character definition, it is extremely important to know more than just bone anatomy.…”
Section: Comparative Craniogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of Hox gene expression patterns based on vertebral morphology has become possible only recently 15 , 28 . The correlation between anterior Hox gene expression and the quantifiable shape of the cervical vertebrae of living archosaurs (crocodile, alligator, and chicken) and mammals (mouse) has shown that changes in the expression of the underlying genetic code can be deduced solely from vertebral morphology 15 , 25 . Furthermore, the correlation observed in extant crocodiles and birds permitted the reconstruction of the vertebral Hox code in an extinct relative that lacks preserved DNA and is known only from fossils remains 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the close phylogenetic relationship to eutherians and the availability of neonates in the pouch (overcoming the difficulties of access when studying in utero development), marsupials can be considered an excellent model to understand the mechanisms that govern cellular differentiation during organogenesis. For instance, different aspects of neocortex development, expansion and evolution have recently been revealed using embryos and neonates of the gray short-tailed opossum (Monodelphis domestica) and of the tammar wallaby (Macropus eugenii) as models [9,10]; while gray short-tailed opossum neonates revealed new insights in the comprehension of bronchioalveolar [11] and chondrocranial development in mammals [12]. The morphological and morphometric study of the skin of marsupial neonates suggested the participation of this organ in gaseous exchange, by the investigation of several species, such as the following: eastern quoll (Dasyurus viverrinus), grey shorttailed opossum (Monodelphis domestica), southern brown bandicoot (Isoodon obesulus), long-nosed bandicoot (Perameles nasuta), brush-tail possum (Trichosurus vulpecula), koala (Phascolarctos cinereus), long-nosed potoroo (Potorous tridactylus), brush-tailed rock wallaby (Petrogale penicillata), red-necked pademelon (Thylogale thetis) and black-striped wallaby (Macropus dorsalis) [13].…”
mentioning
confidence: 99%